P263 Investigation of the first afebrile seizure in the paediatric ED: a systematic review. (June 2019) - Shiwani, Haaris Aziz; MacMeanmain, Eoin; Hurley-O'Dwyer, Evan; Rothwell-Kelly, Grace; Arrotta, Nicholas; Sweeney, Louise; Memon, Danyal; Aziz, Shaheer; Yusuf, Mohammad Danish; Ameen, Hadeer; Molloy, Eleanor
Abstract : Background: There is currently no consensus on investigations required in the paediatric emergency department following a first afebrile seizure. This systematic review aims to compare investigations commonly used and to evaluate their effectiveness and diagnostic value. Methods: In this systematic review keywords such as 'afebrile', 'seizure', 'paediatric' and 'emergency department' were searched for in numerous databases (SCOPUS, MEDLINE, ProQuest, EMBASE, CINAHL, Cochrane and Grey Literature). The resulting titles and abstracts were manually reviewed to exclude irrelevant articles. Finally, the studies that met our inclusion and exclusion criteria were selected to undergo further analysis. Results: A total of eleven articles of the initial 9946 were analysed. Five of these evaluated blood tests (n=303) including full blood count, sodium, potassium, calcium, glucose and leucocytes with no consistent findings. Seven studies evaluated CT or MRI (n=1208). Cumulatively, abnormal results were present in 12.3% of these neuroimaging studies. EEG was also performed in three of the seven studies that performed neuroimaging (n=420) with abnormalities in 37.1% of these. Discussion: In patients presenting to the paediatric emergency department with a first afebrile seizure, thorough history and examination are essential. In unison with the American Academy of Neurology's guidelines, EEG proves to be the most valuable investigation to perform. Neuroimaging may be warranted in some cases to exclude underlying CNS pathology or if structural abnormalities are suspected. Laboratory studies are a necessary adjunct but have limited diagnostic value.